The relative dihedral homology of involutive algebras - Y. Gh. Gouda (International Journal of Mathematics and Mathematical Sciences)
Let f:A→B be a homomorphism of involutive algebras A,B. The purpose of this paper is to define a free involutive algebra resolution of algebra B over f and use it to define and study the relative dihedral homology.